Parental Support in the Process of Choosing a First House (Case Study: Batak Families in Jakarta) - Rossa Turpuk Gabe; Adinda Christina; Angel Ecclesia Shiny; Joko Adianto (Journal of Architectural Research and Design Studies, 2021)
First-time home buyers have many considerations to choose their house after leaving the parental house. One of the determinant roles is culture. Culture influences activities, the meaning of home perspectives, and parental support system. Indonesia has a strong family culture, one of which is the Batak tribe. As one of the largest populations in Jakarta, this study focuses on the next-generation Batak process of selecting the first house. This study using case studies and qualitative research with in-depth interviews. We found that culture influenced the moving stage and parental support role. The parents play two essential parts: they are mindset formers as well as providers of financial support. Although the housing preferences tend to be similar to the firsttime homebuyers in urban areas, culture influences the spatial arrangement process. The finding can contribute to how parental support affects the next generation of migrants while adapts to the housing market.Keywords: Batak family; culture; housing preferences; parental support